2016
DOI: 10.3390/sports4010009
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Jumping Tests versus Wingate Anaerobic Test in Female Volleyball Players: The Role of Age

Abstract: Single and continuous vertical jumping tests, as well as the Wingate anaerobic test (WAnT), are commonly used to assess the short-term muscle power of female volleyball players; however, the relationship among these tests has not been studied adequately. Thus, the aim of the present study was to examine the relationship of single and continuous vertical jumps with the WAnT in female volleyball players. Seventy adolescent (age 16.0 ± 1.0 years, body mass 62.5 ± 7.1 kg, height 170.4 ± 6.1 cm, body fat 24.2% ± 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 24 publications
(28 reference statements)
2
20
0
5
Order By: Relevance
“…From a physiological point of view, core stability tests lasting from 6 s to 230 s had closer affinity with anaerobic capacity (WAnT Pmean and FI) rather than muscle power (Ppeak) and muscle strength. Moreover, it has been observed that exercise duration might partially explain the similar results of two different modes (cycling versus jumping) of exercise tests [21]. With regard to the correlations of the Bosco test, it was observed that the performance on this test correlated moderately-to-largely with torso lateral flexors muscle endurance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…From a physiological point of view, core stability tests lasting from 6 s to 230 s had closer affinity with anaerobic capacity (WAnT Pmean and FI) rather than muscle power (Ppeak) and muscle strength. Moreover, it has been observed that exercise duration might partially explain the similar results of two different modes (cycling versus jumping) of exercise tests [21]. With regard to the correlations of the Bosco test, it was observed that the performance on this test correlated moderately-to-largely with torso lateral flexors muscle endurance.…”
Section: Discussionmentioning
confidence: 96%
“…In exercise testing, the Wingate anaerobic test (WAnT) has been considered as a "golden" standard of anaerobic power and capacity despite its specific mode of exercise (cycling) [19]. A continuous 30 s Bosco jumping test has been developed as more sport-specific than WAnT to monitor performance, especially in sports involving many jumps [20,21]. Therefore, information on the relationship of core stability and symmetry with WAnT and Bosco test would provide insight into the metabolic demands of exercise testing of the former variables.…”
mentioning
confidence: 99%
“…On the other hand, numerous clinical studies demonstrated that children’s muscles are characterized by lower type-II fiber proportion compared to other age groups ( Jansson, 1996 ), while for numerous other studies, these difference are scant ( Belanger and McComas, 1989 ; Davis et al, 2008 ). These characteristics could fully or partly explain difference in anaerobic power between children and adult during high-intensity efforts ( Van and Dore, 2002 ; Dotan et al, 2003 , 2012 ; Nikolaidis et al, 2016a ). Dotan et al (2003) concluded that young men were 24% more powerful per unit body mass than boys, and their lactate levels were 50% greater than levels measured in younger ages.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, most studies investigated correlation between jump test and WAnT in young population ( De Siati et al, 2016 ; Laffaye et al, 2016 ; Nikolaidis et al, 2016a , c ), while few studies have explored the effect of age on this relationship in terms of anaerobic performance. In fact, immaturity of anaerobic metabolism is a main determinant factor that could influence the results of tests and therefore relationship between different aspect of anaerobic performance ( Van and Dore, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation